Optimal Resource Allocation and VCG Auction-Based Pricing for H.264 Scalable Video Quality Maximization in 4G Wireless Systems - Shreyans Parakh; Aditya K. Jagannatham (Advances in Multimedia)
We present novel schemes for optimal OFDMA bitrate allocation towards video quality maximization in H.264 scalable video coding (SVC)-based 4G wireless systems. We use the rate and quality models for video characterization of the SVC extension of the H.264/AVC and develop the framework for optimal scalable video transmission. Subsequently, we derive the closed form solution of the optimal H.264 scalable video quantization parameter for sum video quality maximization in unicast and multicast 4G WiMAX adaptive modulation and coding (AMC) scenarios. We also formulate a Vickrey-Clarke-Groves (VCG) auction-based time-frequency (TF) resource pricing scheme for dynamic bitrate allocation and simultaneous prevention of video quality degradation by malicious users for H.264-based scalable video transmission. Simulation results demonstrate that application of the proposed optimal 4G OFDMA schemes for unicast/multicast video quality maximization yield significantly superior performance in comparison to fixed rate video agnostic allocation.